Role of long non-coding RNAs in metabolic control - Ji, Eunbyul; Kim, Chongtae; Kim, Wook; Lee, Eun Kyung (Biochimica et Biophysica Acta - Gene Regulatory Mechanisms, 2020)
Long non-coding RNAs (lncRNAs) have emerged as pivotal regulators of gene expression by influencing various biological processes including proliferation, apoptosis, differentiation, and senescence. Accumulating evidence implicates lncRNAs in the maintenance of metabolic homeostasis; dysregulation of certain lncRNAs promotes the progression of metabolic disorders such as diabetes, obesity, and cardiovascular diseases. In this review, we discuss our understanding of lncRNAs implicated in metabolic control, focusing on in particular diseases arising from chronic inflammation, insulin resistance, and lipid homeostasis. We have analyzed lncRNAs and their molecular targets involved in the pathogenesis of chronic liver disease, diabetes, and obesity, and have discussed the rising interest in lncRNAs as diagnostic and therapeutic targets improving metabolic homeostasis. This article is part of a Special Issue entitled: ncRNA in control of gene expression edited by Kotb Abdelmohsen.
Keywords: Adipogenesis; Diabetes Mellitus, Type 2; Humans; Non-alcoholic Fatty Liver Disease; Obesity; RNA, Long Noncoding